Influência do estresse nutricional programado na composição da microalga isochrysis galbana - Chagas, Bruna Maria Emerenciano das (2010)
Global warming due to Greenhouse Gases (GHG) emissions, especially CO2, has been identified as one of the major problems of the twenty-first century, considering the consequences that could represent to planet. Currently, biological processes have been mentioned as a possible solution, especially CO2 biofixation due to association microalgae growth. This strategy has been emphasized as in addition to CO2 mitigation, occurs the production of biomass rich in compounds of high added value. The Microalgae show high photosynthetic capacity and growth rate higher than the superior plants, doubling its biomass in one day. Its culture does not show seasons, they grow in salt water and do not require irrigation, herbicides or pesticides. The lipid content of these microorganisms, depending on the species, may range from 10 to 70% of its dry weight, reaching 90% under certain culture conditions. Studies indicate that the most effective method to promote increased production of lipids in microalgae is to induce stress by limiting nitrogen content in the culture medium. These evidences justify research continuing the production of biofuels from microalgae. In this paper, it was studied the strategy of increasing the production of lipids in microalgae I. galbana with programmed nutritional stress, due to nitrogen limitation. The physiological responses of microalgae, grown in f / 2 with different concentrations of nitrogen (N: P 15,0-control, N: 5,0 P and N: P 2,5) were monitored. During exponential phase, results showed invariability in the studied conditions. However the cultures subjected to stress in stationary phase, showed lower biomass yields. There was an increase of 32,5% in carbohydrate content and 87.68% in lipids content at N: P ratio of 5,0 and an average decrease of 65% in protein content at N: P ratios of 5, 0 and 2.5. There were no significant variations in ash content, independently of cultivation and growth phase. Despite the limitation of biomass production in cultures with N: P smaller ratios, the increase of lipid accumulation highest lipids yields were observed as compared to the control culture. Given the increased concentration of lipids associated to stress, this study suggests the use of microalgae Isochrysis galbana as an alternative raw material for biofuel production